Mouse Model of Microembolic Stroke and Reperfusion - Atochin, Dmitriy; Murciano, Juan Carlos; Gursoy-Özdemir, Y.; Krasik, Tatiana; Noda, F.; Ayata, C.; Dunn, A.K.; Moskowitz, M.A.; Huang, Paul L.; Muzykantov, Vladimir R. (My University, 2004)
Background and Purpose¿To test the role of fibrinolysis in stroke, we used a mouse model in which preformed 2.5- to 3- m-diameter fibrin microemboli are injected into the cerebral circulation. The microemboli lodge in the downstream precapillary vasculature and are susceptible to fibrinolysis. Methods¿We injected various doses of microemboli into the internal carotid artery in mice and characterized their distribution, effects on cerebral blood flow, neurological deficit, infarct area, and spontaneous dissolution. By comparing wild-type and tissue plasminogen activator (tPA) knockout (tPA / ) mice, we analyzed the role of endogenous tPA in acute thrombotic stroke. Results¿Microemboli cause dose-dependent brain injury. Although moderate doses of microemboli are followed by spontaneous reperfusion, they result in reproducible injury. Gene knockout of tPA markedly delays dissolution of cerebral emboli and restoration of blood flow and aggravates ischemic thrombotic infarction in the brain. Conclusions¿We describe a microembolic model of stroke, in which degree of injury can be controlled by the dose of microemboli injected. Unlike vessel occlusion models, this model can be modulated to allow spontaneous fibrinolysis. Application to tPA / mice supports a key role of endogenous tPA in restoring cerebral blood flow and limiting infarct size after thrombosis. (Stroke. 2004;35:2177-2182.) Key Words: animal models fibrinolysis microemboli stroke stroke, embolic